Prevalence of Gestational Hypertension and Pregnancy Outcome - Bhat AV; Kharde SN (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction Hypertension during pregnancy is considered as one the high risk as it is one of the cause for maternal and neonatal mortality and morbidity. Aims: This study is aimed to find the prevalence of gestational hypertension and to understand the pregnancy outcome. Settings and Design: Study conducted at tertiary care hospital and descriptive research design was used for the study Methods and Material: Sample size was 366 women with gestational hypertension were included. Data was collected by using investigator prepared self-administered questionnaire Statistical analysis used: inferential statistics analytical methods Results: Results revealed that prevalence of gestational hypertension 9.8%. Maternal outcome 53% delivered at 34 to 38 weeks, mode of delivery (52.5%) were delivered by C-section, 56.3% women were induced, 97.3% were singleton pregnancy, About the gender of new-born 51.9% were male, 67.2% were born with Normal (>2500g) weight, NICU admission 20.5% and reason for NICU admission was prematurity. Conclusions: The knowledge of risk factors for gestational hypertension in pregnancy may give tracks for prevention in this population.